Epidemiology of Cardiovascular Diseases in Regions of Russian Federation. Third survey (ESSE-RF-3). Rationale and study design - O. M. Drapkina; S. A. Shalnova; A. E. Imaeva; Yu. A. Balanova; S. A. Maksimov; G. A. Muromtseva; V. A. Kutsenko; N. S. Karamnova; S. E. Evstifeeva; A. V. Kapustina; E. B. Yarovaya; O. A. Litinskaya; et al. (Кардиоваскулярная терапия и профилактика)
Previous studies have shown significant differences in the health status of the population depending on the place of residence. Despite the ongoing preventive measures, there is no improvement in the epidemiological situation in relation to noncommunicable diseases, including due to unfavorable living conditions. This study is a continuation of the following earlier studies: Epidemiology of Cardiovascular Diseases in Regions of Russian Federation (ESSE-RF) and ESSE-RF-2.Aim. To assess the prevalence of cardiovascular diseases, various risk factors (RFs) of these diseases and their association in Russian regions with different economic, climate and geographic characteristics to determine the risk profile of the region and develop approaches to targeted prevention programs specific to the regions.Material and methods. The study selected 30 regions representing each federal district of the Russian Federation. The survey of participants is carried out in three stages as follows: survey using an original modular questionnaire; measurements, including anthropometry, hand grip strength test, blood pressure and heart rate assessment; blood sampling, followed by biobanking and laboratory tests.Conclusion. The results obtained will allow deepening knowledge about the RF profile specific to a particular region, evaluating the effectiveness of preventive programs, and planning new ones taking into account regional and socio-demographic characteristics. This will become the basis for a better understanding of the socio-economic burden of noncommunicable diseases and the economic damage of RFs.